PENGARUH DARK TRIAD PERSONALITY DALAM SERIAL DRAMA LAYANGAN PUTUS: Studi Analisis Psikologi Kepribadian dan Psikologi Tasawuf - Afni Handayani; Abdul Basit Atamimi (Jurnal An-Nufus, 2022)
This research discusses the characters characterized by dark triad personality in a television series entitled Layangan Putus. This drama series was inspired by a true story of a woman that went viral on social media. The story went viral because it featured a story of infidelity in marital life. Dark triad personality is the side of human personality that appears and is visible to others and cannot be directly known. The structure of the characters in this series consists of machiavellianism, narcissism and psychopathy; three traits that exist in the dark triad personality. These three characters are what attracted the author to research. The author summarizes the figures and characters in this drama story as individuals who care less about interpersonal relationships, often neglecting morals, norms and ethics. To limit the perspective in analyzing the case, we discuss it from the point of view of personality psychology and Sufism psychology. This research uses a qualitative method by analyzing the content of the story. Processing and extracting data using observation and documentation techniques. Some of the findings that we found include: The side of human personality that appears and is seen by others cannot be directly known; Nafs is not present in the visible form, but comes from the results of the interaction process between the spirit and the human self.